Reinforcement of the Halal Industry for Global Integration Revival: Proceedings of the 2nd International Conference on Halal Development (ICHaD 2021), Malang, Indonesia, 5 October 2021 - International Conference on Halal Development; Pratikto, Heri; Nasih, Ahmad; Isma'il, Zawawi; Voak, Adam (Routledge, 2023)
The emergence of a Halal industry in the past decade in the fields of food, beverages, and services, emphasizes the importance of providing a more complete understanding of Halal products, current Halal developments and other topics of Halal development. This groundbreaking volume provides theoretical and empirical studies on the Halal industry. This book explores critical issues, best practice examples, and draws on a range of international case studies to demonstrate theory in practice of the Halal industry. Emphasizing the Halal industry, the chapters address a number of important issues such as Halal assurance system, Halal product certification, Halal tourism, Human Resources of Halal Certification, supply chain of Halal products, and other related subjects. This book will be of interest to students, scholars, and practitioners who have a deep concern and interest in the Halal industry. It is futuristic with a lot of practical insights for students, faculty members, and practitioners. Since the contributors are from across the globe, it is fascinating to see the global benchmarks.